Studying night work and disease in the Million Women Study. (19th October 2011) - Wang, Xiao Si; Travis, Ruth; Beral, Valerie
Abstract : Objectives: To assess the association between night work and risk of cancer and cardiovascular disease, we are collecting data on night work and other related exposures in a large UK prospective study. Methods: 1.3 million women aged 50–69 years old were recruited into the Million Women Study during 1996–2000 in England and Scotland. The 2009 follow-up questionnaire included questions on a number of factors including previous night work, chronotype, usual sleep duration, and sleep difficulties. Women also provided data on a range of other personal characteristics. Results: We will describe the study and present results from cross-sectional analyses on the characteristics of night workers compared to non-night workers. Preliminary results show that women who have ever worked at night differ with respect to a number of major risk factors for breast cancer and ischemic heart disease, in that they are more obese, smoke more, and are more likely to come from lower socioeconomic groups, to have ever used hormone replacement therapy and to report having poor sleep quality. Conclusions: Women who have worked at night have different characteristics from those who have not, which would put them at increased risk of breast cancer and cardiovascular disease.